The cytotoxic and apoptotic effects of wild and polyploidy genotype of Artemisia cina extracts on the WiDr colon and HTB-183 lung cancer cell lines - Elizabeth Kristiani; Sri Kasmiyati; Maria Herawati (Society for Indonesian Biodiversity, 2021)
Abstract. Kristiani EBE, Kasmiyati S, Herawati MM. 2021. The cytotoxic and apoptotic effects of wild and polyploidy genotype of Artemisia cina extracts on the WiDr colon and HTB-183 lung cancer cell lines. Biodiversitas 22: 2844-2852. Artemisia belongs to the Asteraceae family, usually used for traditional treatments of various diseases in China. Artemisia cina Berg ex Poljakov, which lots found in Indonesia, has not been studied much like a cancer drug. The research aims were (i) to compare the bioactive content of hexane and ethyl acetate extract of wild (TWN and KJT) and polyploidy type (J and M) of A. cina and its cytotoxicity on WiDr and HTB-183 cancer cells, (ii) to evaluate the cytotoxicity mechanism of the most substantial extract of it. All of the extracts were prepared by maceration methods using hexane and ethyl acetate separately. The research method used was quantitative with experimental design. The determination of quercetin, kaempferol, and artemisinin used HPLC. The cytotoxicity of the extract determined using the MTT method. The assay of the specific protein related to apoptosis using ICC assay. The content of three bioactive compounds on ethyl acetate extracts higher than hexane extract, in which the extract of J and KJT genotypes had higher levels than M and TWN genotypes. The IC50 value (µg/mL) of extracts against cancer cell lines tested was about 400-700 hexane extracts and 200-500 ethyl acetate extracts. The BCl-2 expressions of both cancer cell lines decreased by treating TWN-EA and M-EA, while the P53 expressions increased. The TWN-EA induced apoptosis of HTB-183 cell lines through caspase-8 and caspase-9 pathways, but M-EA induced caspase-9 pathway only. The TWN and M genotypes were potential to use as anticancer agents on colon and lung cancer.